CONVERSION OF OIL RECOVERED FROM PALM OIL MILL EFFLUENT (POME) INTO BIODIESEL USING ELECTROLYSED CARBON CATALYST - Balan, Winnie; Janaun, Jidon; Siambun, Nancy (MATTER: International Journal of Science and Technology, 2017)
Malaysia produces approximately 60 million tons of palm oil mill effluent (POME) annually. Raw POME contains 0.6-0.7% oil and it has high free fatty acids (FFAs). The residual oil in POME however, is a potential feedstock in biodiesel production. Oil in the POME was recovered and converted into biodiesel through catalysis esterification reaction. A new carbon based catalyst had been developed in this study. Carbon deposited from electrolysis process was used as carbon precursor to synthesis electrolysis carbon catalyst (CEC). The carbon was sulfonated using concentrated sulfuric acid at temperature 150 °C for 12 h followed by washing and drying of the sulfonated carbon (CEC). CEC was characterized for its physiochemical properties using Elemental analyzer, FT-IR, SEM-EDX, TGA-DTA and back titration methods. Elemental analysis results showed that S content in CEC was ~4 times higher than the electrolysis carbon. The FT-IR detected the presence of weak sulfonic acid groups. The total acidity of CEC was 0.75 mmol g-1 suggesting poor acid functionalization of the electrolysis carbon. This could be associated with the stability of the carbon and also the presence of other elements that weaken the sulfonation reaction. The structure of CEC was observed through the SEM images. CEC possessed a randomly ordered structure and discrete microporous pores.Catalytic activity of CEC was tested on esterification of oil recovered from POME with methanol. The yield was very low, which was 6.19%, this was attributable to the low active sites of the CEC. Further improvement on the electrolyze carbon need to be done in order to increase the total acidity.